2022
DOI: 10.3390/biomedicines10102640
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Role of ACVR1/ALK2 in Basal and TGFβ1-Induced Cell Migration in Pancreatic Ductal Adenocarcinoma Cells and Identification of a Self-Perpetuating Autoregulatory Loop Involving the Small GTPase RAC1b

Abstract: Pancreatic ductal adenocarcinoma (PDAC) cells are known for their high invasive/metastatic potential, which is regulated in part by the transforming growth factor β1 (TGFβ1). The involvement of at least two type I receptors, ALK5 and ALK2, that transmit downstream signals of the TGFβ via different Smad proteins, SMAD2/3 and SMAD1/5, respectively, poses the issue of their relative contribution in regulating cell motility. Real-time cell migration assays revealed that the selective inhibition of ALK2 by RNAi or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…These inflammatory cells produce various cytokines (23). In combination with TGFβ1, these cytokines induce the migration of fibroblasts, epithelial cells, and endothelial cells (24)(25)(26)(27). Thrombin and factors of the fibrinolytic system increase vascular permeability (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…These inflammatory cells produce various cytokines (23). In combination with TGFβ1, these cytokines induce the migration of fibroblasts, epithelial cells, and endothelial cells (24)(25)(26)(27). Thrombin and factors of the fibrinolytic system increase vascular permeability (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…In light of the Thakur study highlighting stromal BGN as a TGF-β inhibitor and tumor suppressor in a murine model of human PDAC, we were especially interested in revealing if all three proteins do affect TGF-β signaling. Previous data from our group revealed that RAC1b negatively controls TGF-β signaling via the ALK2-SMAD1/5 arm [21] with inhibition of RAC1b in PANC-1 cells via RNAi-mediated knockdown or genomic knockout causing elevated levels of C-terminally phosphorylated SMAD1/5 (pSMAD1/5) after TGF-β1 treatment. In order to reveal whether TAp73 or BGN can mimic this effect, we transfected PANC-1 cells with siRNA to p73 or BGN and after a 1 h stimulation with TGF-β1 measured the abundance of pSMAD1/5 by phospho-immunoblotting.…”
Section: Identification Of Downstream Targets and Signaling Pathways ...mentioning
confidence: 97%
“…RAC1b negatively controls TGF-β signaling via the ALK2-SMAD1/5 arm [21] with inhibition of RAC1b in PANC-1 cells via RNAi-mediated knockdown or genomic knockout causing elevated levels of C-terminally phosphorylated SMAD1/5 (pSMAD1/5) after TGF-β1 treatment. In order to reveal whether TAp73 or BGN can mimic this effect, we transfected PANC-1 cells with siRNA to p73 or BGN and after a 1 h stimulation with TGF-β1 measured the abundance of pSMAD1/5 by phospho-immunoblotting.…”
Section: Identification Of Downstream Targets and Signaling Pathways ...mentioning
confidence: 99%